PENGARUH EMPLOYER BRANDING DAN REPUTASI PERUSAHAAN TERHADAP ORGANIZATIONAL ATTRACTIVENESS DI PERUSAHAAN STARTUP PADA GENERASI Z - Shafara Arifah Phalevi; Seger Handoyo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Global economic development, the phenomenon of layoffs, and the threat of a global recession accelerate market disruption significantly, making it difficult for startups to attract employees to gain a competitive advantage in the intensifying talent war. To overcome this, startups have the challenge of improving post-layoff strategies by conducting employer branding and improving the company's reputation so that potential employees are interested in working at startups, so this study aims to determine whether there is an effect of employer branding and company reputation on organizational attractiveness in startup companies in Generation Z. The method used in this study is a survey method and obtained 223 respondents who are generation Z who were born in the range of 1997 - 2005 or currently 18-26 years old. The results obtained from this study employer branding and company reputation affect organizational attractiveness based on the results of the coefficient of determination analysis test, it is known that R square in the summary model is 0.631 or 63.1% employer branding and company reputation affect organizational attractiveness, while 36.9% is influenced by other factors not examined in this study.